Acquaintance, attitude, and perceived barriers regarding scientific research publications among clinical nurses: a cross-sectional study at tertiary care hospitals in western Rajasthan - Kalal, Nipin; Vel, N. sabari; Chaudhary, Saroj; Meena, Savita; Meena, Sonam; Bhichar, Sonu; Singh, Spraha (Frontiers in Research Metrics and Analytics, 2024)
Introduction: In today's era, conducting research is crucial for advancing the nursing profession. Scientific publications in clinical research aim to improve patient care outcomes and foster a sense of importance for nurses within the healthcare team. However, clinical nurses often lag due to factors such as limited familiarity, attitudes towards research, and encountered barriers. Objectives: The study conducted to know the knowledge, attitude, and perceived barriers regarding scientific research publication among clinical nurses at tertiary care hospitals in western Rajasthan. Methodology: A Cross-sectional descriptive study was conducted among the clinical nurses. Participants were assessed for their knowledge, attitude, and perceived barriers regarding scientific research publications through a self-administered questionnaire. Results: The study revealed that 92% of participants lacked sufficient knowledge about scientific research publications, and 78.3% had a moderate perception of barriers. Pearson's correlation coefficient indicated a weak positive correlation (r= 0.143, p= 0.007) between knowledge and attitude, and a significant negative correlation (r= -0.143, p= 0.012) between knowledge and perceived barriers. However, multiple linear regression analysis showed no significant relationship among clinical nurses in terms of knowledge, attitude, and perceived barriers towards scientific research publication. Conclusion: A study on clinical nurses revealed that a majority have insufficient knowledge about scientific research, while over half hold neutral attitudes toward research publications. Additionally, a significant portion of clinical nurse's report experiencing moderate levels of perceived barriers.